Analisis Sistem Penilaian Kinerja Karyawan dalam Meningkatkan Kualitas Sumber Daya Manusia pada Bengkel Pusat PTPN II - Fajar Hidayah Tullah; Alfahmi, Muhammad; Nashrudin Setiawan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to analyze the employee performance evaluation system used at the PTPN II central workshop. This research includes data collection through interviews with managers and employees as well as analysis of relevant documents. The research results show that the current PTPN II Workshop employee performance appraisal system has several weaknesses, namely the lack of quality of employee performance appraisal in the areas of skills, personal, soft skills and hard skills. The evaluation process is not always objective, the assessment criteria are unclear and the comments provided are not systematic. Additionally, there is a need to improve employee training and development based on their performance appraisal. Recommendations include establishing clearer evaluation criteria, training managers to provide effective feedback, and improving the employee development system to determine the objectives of research on employee performance and quality in the areas of personal skills, soft skills and hard skills. It is hoped that this will help improve the quality of employee performance assessments and their contribution to the success of the PTPN II focus workshop. This study provides useful information for other organizations seeking to improve their employee performance appraisal systems and also provides guidance for improving overall human resource management.